APPLICATION OF THE TERM "SELF-GOVERNMENT": RUSSIAN, SOVIET AND YUGOSLAVIAN EXPERIENCE - Sergeev D.B. (Scientific Journal of Pedagogy and Economics, 2019)
. Research objective is the historical and legal research application of the term "local self-government" in the legislation of the Russian Empire, the Russian Soviet Federative Socialist Republic, the Union of Soviet Socialist Republics, the Russian Federation and the Socialist Federal Republic of Yugoslavia. The content of legal history of local self-government in the Russian Empire, RSFSR, USSR, the Russian Federation and Yugoslavia (the provisions on the peasants who left serfdom of the Russian Emperor Alexander II 1861, The Decree of Soviet of People’s Commissars of RSFSR about Establishment of the Commissariat on Selfgovernment of 1917, Letter of the People’s Commissariat for Internal Affairs of RSFSR "About the Organization of Self-government" 1917, Constitution of the USSR 1977, Law of the USSR of "About the General Principles of Selfgovernment and Local Economy in the USSR" 1990, Constitution of RSFSR 1978, Constitution of the Russian Federation 1993, Constitution of the Socialist Federal Republic of Yugoslavia 1974 and Federal Laws of the Russian Federation "About the General Principles of Self-government in the Russian Federation" 1995 and 2003) and the works of legal scientists are studied using the historical legal method and synthesis. It is noted that as the self-government is activity, not absolutely to call this institute the fundamental principle of the organization of society, state. More logical as a basis of the constitutional system to consider obligation of functioning and security of local government in this connection it is necessary updating of the Russian legislation.